Siti Maftukhah Potensi Sabut Kelapa dan Serbuk Gergaji sebagai Bioadsorben Timbal dan Methylene Blue - siti Maftukhah; Dine Agustine; Ryan Andry Saputra; Mutia Amyranti; Lily Arlianti; Ismi Nurlatifah (UNISTEK, 2026)
Waste processing of chemical, paper and textil industria is still a problem in aquatic ecosystems, especially difficulties in utilization and disposal. One of the wastes that is difficult to be degraded by nature is lead and methylene blue dye. Coconut fiber and sawdust are waste from human activities that have the potential as bioadsorbents for lead and methylene blue waste. The purpose of this study was to determine the ability of coconut fiber and sawdust as bioadsorbents for lead and methylene blue. The methods in this study were sample preparation, carbonization, bioadsorbent activation, artificial waste solution creation, application, and analysis. The results obtained by coconut fiber and sawdust in adsorbing lead and methylene blue with the highest absorption in the composition of 25%: 75%; 50% ; 50% on lead with a lead content of 1.13 mg/l and an absorption capacity of 96.70% and a composition of 50%: 50% on methylene blue with a methylene blue content of 1.15 mg/l and an absorption capacity of 89.95%. The mathematical modeling to determine the closest adsorption capacity is Langmuir adsorption isotherm with linear regression line equation of y = 0.0658x + 0.0956 with an R2 value of 0.7952 for lead and y = 0.1101x + 0.6155 with an R2 value of 0.7920 for methylene blue. The results of this study indicate that coconut fiber and sawdust have the potential as bioabsorbents for lead and methylene blue.